ANALISIS GENRE WACANA SURAT HAMID KEPADA ZAINAB DALAM NOVEL DI BAWAH LINDUNGAN KA’BAH - Miftah Wangsadanureja; Ika Juhriati; Muhammad Arif Muchlisin (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study will examine the genre analysis of the contents of Hamid's letter to Zainab contained in the novel "Di bawah Lindungan Ka’bah" by Buya Hamka. The subject of this research is Hamid's letters. The object of research is genre. The data obtained is the documentation of their letters contained in the novel. The method used to analyze the data is a qualitative descriptive method. Data analysis uses genre theory because it can conclude the analysis from the types of discourse, as well as describe its substance. The results showed that Hamid's letter to Zainab contained 6 purpose sentences, 1 rhetorical structure. Meanwhile, for the realization of the use of linguistic forms using the LFS (Systemic Functional Linguistics) method, there are data; Mental processes = 9 processes, Material processes = 11 processes, behavioral processes = 2 processes, relational processes = 5 processes. Then after conducting further analysis of this research, we can conclude that Hamid's letter to Zainab belongs to the type of descriptive discourse